Midwives’ knowledge and utilization of non-pneumatic anti shock garment in reducing complication of postpartum haemorrhage in selected health care facilities in Bayelsa state Nigeria - Onasoga, Olayinka A.; Duke, Emon; Danide, Imabin U.; Jack-Ide, Izibeloko Omi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Non-pneumatic anti-shock garment (NASG) is a first-aid lower-body pressure device that reverses hypovolaemic shock and decreases obstetric hemorrhage thereby decreasing maternal morbidity and mortality due to post-partum haemorrhage (PPH).This study assessed the knowledge and utilization of non-pneumatic anti shock garment in the management of postpartum hemorrhage among midwives in selected health care facilities in Bayelsa state. Methods: This is a descriptive cross-sectional study in which a sample size of 112 nurses were selected using purposive sampling technique. The instrument for data collection was questionnaire and data collected were analyzed using descriptive and inferential statistics. Results: The study revealed that majority of the respondents regardless of their educational level had good knowledge of the description, mechanism of action, and uses of NASG. It was also revealed that majority of the respondents do not use NASG in their centers and its application in management of post-partum hemorrhage was not part of the protocols in these centers, which was a clear indication of underutilization of the NASG in the primary health care centers. There was no significant association found between years of working experience of respondents and their utilization of NASG with (X2 = 8.577, df = 2, P = 0.114) as well as between the level of knowledge of midwives and their utilization of the NASG with (X2 = 0.387, df = 1, P = 0.534). Conclusions: It was recommended that non-pneumonic antishock garment should be made available by government and its utilization should be included in all health care centers policy as a management protocol for post-partum hemorrhage.